Border gateway protocol to enhance failover in multihoming environment - Ahmed, Muhammed Zaharadeen (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Nowadays the need for a reliable Internet access across the globe is very crucial because of the huge size of useful data it stores. This stimulates most ISPs to choose a reliable routing protocol such as Border Gateway Protocol in order to ensure guarantee of customer's data on the Internet. By multi-homing a network using BGP, a more control of logical division of the traffic load and achieving failover becomes possible. This enhances network performance, throughput and provide better routing policies on the Internet. Single-homed Internet communication link for an ISP networks does not inspire with confidence because of excessive traffic and device/human errors that may arise. BGP is used because of its ability to choose the best path to a destination particularly in a Multihoming environment. Link fault tolerance is highlighted on its challenge to Multihoming network. Simulation of BGP network was carried out on single homing where the result presents limited reliability in guarantee of customer's data. Alternatively, two independent simulations were carried out to run BGP Multihoming to the same Internet service provider and to different Internet service provider in other to provide an improvement. In BGP Multihoming to the same Internet Service Provider, a failover technique was introduced to providing realizing reliability on the network while the technique of traffic division was introduced in realizing scalability. Also, in simulating BGP Multihoming to different ISP, the technique of providing failover was ensured by realizing reliability while network analysis was carried out to ensure the throughput in the network. In ensuring the throughput, 6 routers were benchmarked in AS 100 to perform the analysis. At the end, simulation results were achieved using Graphical Network Simulator 3 emulator and Wireshark network analyzer. The simulation was carried out to show an improvement in reliability and scalability of the BGP network.